ANALISIS STUDI KELAYAKAN PENGEMBANGAN USAHA KRIPIK TORTILLA DI PT LMA BALI KREATIF (LA BLOSSOM) - Klaudionisius Morgani; I Desak Putu Kartika Pratiwi (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the feasibility of developing the Tortilla Chips business at PT LMA Bali Kreatif (LA Blossom) located in Bali. The analysis evaluates six main aspects: market, technical, legal, management, environmental, and financial. The results show that market demand for this product is high, particularly among tourists interested in vegan and gluten-free products. The technical aspect highlights that the strategic business location and abundant local resources support smooth production. From the management aspect, the company has an efficient organizational structure. Financially, the business shows promising prospects with a positive NPV, high IRR, and a quick Payback Period, indicating that the development of the Tortilla Chips business is feasible to continue.